Growth and Inequality in Public Good Games - Simon Gächter; Friederike Mengel; Elias Tsakas; Alexander Vostroknutov (Institute for the Study of Labor (IZA), 2014)
In a novel experimental design we study public good games with dynamic interdependencies. Each agent's income at the end of a period serves as her endowment in the following period. In this setting growth and inequality arise endogenously allowing us to address new questions regarding their interplay and effect on cooperation levels. In stark contrast to standard public good experiments, we find that contributions are increasing over time even in the absence of punishment possibilities. Inequality and group income are positively correlated for poor groups, but negatively correlated for rich groups. There is very strong path dependence: inequality in early periods is strongly negatively correlated with group income in later periods. These results give new insights into why people cooperate and should make us rethink previous results from the literature on repeated public good games regarding the decay of cooperation in the absence of punishment.
Keywords: C92; H41; D63; 330; public goods; inequality; growth